RETRACTED: Development of methods and algorithms for calculating ventilation and perfusion in the EIT - Aleksanyan Grayr; Gorbatenko Nikolay; Kucher Artyom; Katsupeev Andrey (BIO Web of Conferences, 2024)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001